2002
DOI: 10.1046/j.1460-9568.2002.01892.x
|View full text |Cite
|
Sign up to set email alerts
|

GDNF and NGF released by synthetic guidance channels support sciatic nerve regeneration across a long gap

Abstract: The present work was performed to determine the ability of neurotrophic factors to allow axonal regeneration across a 15-mm-long gap in the rat sciatic nerve. Synthetic nerve guidance channels slowly releasing NGF and GDNF were fabricated and sutured to the cut ends of the nerve to bridge the gap. After 7 weeks, nerve cables had formed in nine out of ten channels in both the NGF and GDNF groups, while no neuronal cables were present in the control group. The average number of myelinated axons at the midpoint o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
198
1
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 269 publications
(208 citation statements)
references
References 76 publications
6
198
1
3
Order By: Relevance
“…Several studies using cell free synthetic nerve grafts examined the effects of different growth factors on peripheral nerve repair across long gaps including FGF-2 (Aebischer et al, 1989), BDNF andNT-3 (Xu et al, 1995), and GDNF and NGF (Fine et al, 2002). Short-term studies of our own group showed that a cellular substrate like transplanted genetically modified Schwann cells over-expressing FGF-2 isoforms is a promising tool to promote Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies using cell free synthetic nerve grafts examined the effects of different growth factors on peripheral nerve repair across long gaps including FGF-2 (Aebischer et al, 1989), BDNF andNT-3 (Xu et al, 1995), and GDNF and NGF (Fine et al, 2002). Short-term studies of our own group showed that a cellular substrate like transplanted genetically modified Schwann cells over-expressing FGF-2 isoforms is a promising tool to promote Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, nerve fiber regeneration was also enhanced at the proximal coaptation site, but it did not persist across the distal coaptation site of a 20-mm gap (Rovak et al, 2004). Nerve growth factor (NGF) and glia-derived neurotrophic factor (GDNF), respectively, continuously released by synthetic guidance channels bridging a 15-mm gap in rat sciatic nerves showed different effects on the regeneration of myelinated sensory and motor axons as well as unmyelinated axons (Fine et al, 2002). NGF entrapped in microspheres loaded into synthetic nerve guides bridging a 10-mm gap in rat sciatic nerves showed good regeneration of myelinated fibers also, according to fiber diameter, fiber population, and grade of myelination (Xu et al, 2003).…”
Section: Role Of Fgf-2 Isoforms Within the Regeneration Scenariomentioning
confidence: 99%
See 1 more Smart Citation
“…[30][31][32][33] However, there have been major problems in delivering neurotrophic factors into the nervous system, such as the serum half-life of the recombinant protein may be short and the blood-brain barrier limits access to the central nervous system. This study provided evidence for the beneficial effects of BMP7 gene transfer on the regeneration/protection of the injured sciatic nerves in rats and raised the possibility of developing BMP7 gene transfer as a potential neuroprotective agent for peripheral nerve repair applications.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, research has been focused mainly on improving the single lumen nerve tube to bridge larger nerve gaps (de Ruiter, Malessy, Yaszemski, Windebank, & Spinner, 2009;de Ruiter, Spinner, Yaszemski, Windebank, & Malessy, 2009). The artificial conduit may be implanted empty, or it may be filled with collagen and laminin-containing gels (Labrador, Buti, & Navarro, 1998;Madison, Da Silva, & Dikkes, 1988;Verdu et al, 2002), internal frameworks (de Ruiter, Spinner et al, 2009;Francel, Francel, Mackinnon, & Hertl, 1997;Lundborg & Kanje, 1996;Meek et al, 2001;Nakamura et al, 2004;Yoshii & Oka, 2001;Yoshii, Oka, Shima, Taniguchi, & Akagi, 2003), supportive cells (Ansselin, Fink, & Davey, 1997;Evans et al, 2002;Guenard, Kleitman, Morrissey, Bunge, & Aebischer, 1992;Kim et al, 1994;Rodriguez, Verdu, Ceballos, & Navarro, 2000;Sinis et al, 2005), growth factors (Derby et al, 1993;Fine, Decosterd, Papaloizos, Zurn, & Aebischer, 2002;Hollowell, Villadiego, & Rich, 1990;Lee et al, 2003;Midha, Munro, Dalton, Tator, & Shoichet, 2003;Sterne, Brown, Green, & Terenghi, 1997), and conductive polymers, but combinations have also already been used (Figure 2). An artificial graft can meet many of the needs of regenerating fibres by concentrating neurotrophic factors, reducing cellular invasion and providing directional neuritis outgrowth to prevent neuroma formation.…”
Section: Nrg1 To Promote Nerve Repair Peripheral Nerve Injury and Repairmentioning
confidence: 99%